Effects of vitamin D supplementation on intestinal permeability, cathelicidin and disease markers in Crohn's disease: Results from a randomised double-blind placebo-controlled study. Issue 3 (June 2015) - Raftery, Tara; Martineau, Adrian R; Greiller, Claire L; Ghosh, Subrata; McNamara, Deirdre; Bennett, Kathleen; Meddings, Jon; O'Sullivan, Maria
Background: Vitamin D (vitD) supplementation may prolong remission in Crohn's disease (CD); however, the clinical efficacy and mechanisms are unclear. Aim: To determine changes in intestinal permeability (IP), antimicrobial peptide (AMP) concentrations and disease markers in CD, in response to vitD supplementation. Methods: In a double-blind randomised placebo-controlled study, we assigned 27 CD patients in remission to 2000 IU/day vitD or placebo for 3 mos. We determined IP, plasma cathelicidin (LL-37 in ng/mL), human-beta-defensin-2 (hBD2 in pg/mL), disease activity (Crohn's Disease Activity Index (CDAI)), C-reactive protein (CRP in mg/L), fecal calprotectin (µg/g), Quality of Life (QoL) and serum 25-hydroxyvitamin D (25(OH)D in nmol/L) at 0 and 3 mos. Results: At 3 mos., 25(OH)D concentrations were significantly higher in those whom were treated ( p  < 0.001). Intra-group analysis showed increased LL-37 concentrations ( p  = 0.050) and maintenance of IP measures in the treated group. In contrast, in the placebo group, the small bowel ( p  = 0.018) and gastro-duodenal permeability ( p  = 0.030) increased from baseline. At 3 mos., patients with 25(OH)D ≥ 75 nmol/L had significantly lower CRP ( p  = 0.019), higher QoL ( p  = 0.037), higher LL-37 concentrations ( p  < 0.001) and non-significantly lower CDAI scores ( p  = 0.082), compared to those with levels <75 nmol/L. Conclusion: Short-term treatment with 2000 IU/day vitD significantly increased 25(OH)D levels in CD patients in remission and it was associated with increased LL-37 concentrations and maintenance of IP. Achieving 25(OH)D ≥ 75 nmol/l was accompanied by higher circulating LL-37, higher QoL scores and reduced CRP. Registered at ClinicalTrials.gov (NCT01792388).